Predictors of frequent attenders of emergency department at an acute general hospital in Singapore. Issue 11 (14th May 2010) - Paul, P; Heng, B H; Seow, E; Molina, J; Tay, S Y
Abstract : Objective: To determine factors associated with frequent emergency department (ED) attendance at an acute general hospital in Singapore. Method: Patients who attended the ED from 1 January to 31 December 2006 without prior attendance in the preceding 12 months (index attendance) were tracked for 12 months. Variables included in the analysis were age, gender, race, date and time of attendance, patient acuity category scale, mode of arrival, distance to ED and diagnosis based on ICD-9CM code. Frequent attenders were patients who attended the ED ≥5 times for any diagnosis within 12 months. Results: A total of 82 172 patients in the study cohort accounted for a total of 117 868 visits within 12 months, of which 35 696 (30.3%) were repeat attendances. A total of 1595 patients (1.9%) were frequent attenders responsible for 8% of all repeat attendances. Stepwise logistic regression analysis found patients aged 75+ years, male, non-Chinese ethnic groups, Sunday and Monday, time of the attendance from 16:00 to midnight, distance to ED, chronic obstructive pulmonary disease, heart failure and acute respiratory infections to be significantly associated with frequent attendances. Conclusion: With the ageing population and their complex healthcare needs, elderly patients with chronic medical conditions are expected to make up an increasing proportion of the workload of ED in the future. A systems approach and a disease and case management approach in collaboration with primary care providers are interventions recommended to stem this.